Cardiovascular Complications of COVID-19: Review of Cardiac Injury Pathophysiology and Clinical Evidence - Olga V. Rasputniak; Tetiana I. Gavrilenko; Olena A. Pidgaina; Olena M. Trembovetska; Oleksandr M. Lomakovskyi; Liudmyla M. Shnaider (Ukrainian Journal of Cardiovascular Surgery, 2024)
The coronarovirus disease 2019 (COVID-19) pandemic is still a significant cause of morbidity and mortality, with a rapidly increasing number of infections and deaths worldwide. The possibility of heart involvement in patients with COVID-19 has received great attention since the beginning of the pandemic. In the present review, we summarize the current knowledge on myocardial involvement in COVID-19, provide an overview of the incidence, pathogenetic mechanisms and clinical implications of cardiac injury in this setting.Recent evidence suggests an interplay between COVID-19 and cardiovascular diseases. Cardiac involvement plays a key role in the management and prognostication of patients with SARS-CoV-2 infection. Heart failure is a common state that can be encountered at different stages in the course of COVID-19 patient presentation. New or existing heart failure in the setting of COVID-19 can present a set of unique challenges that can complicate presentation, management andprognosis. It is still unclear whether heart failure in COVID-19 is due to direct effect of SARS-CoV-2 on the myocardium or it is indirectly caused by hypoxia, cytokine release, volume overload, overwhelming critical illness. Careful understandingof hemodynamic and diagnostic implications is essential for appropriate triage and management of these patients. Abnormal cardiac biomarkers are common in COVID-19 and can stem from variety of mechanisms that involve the viral entry itself through angiotensin I converting enzyme 2 receptors, direct cardiac injury, increased thrombotic activity,stress cardiomyopathy etc. Data on the impact of COVID-19 in chronic heart failure patients and its potential to trigger acute heart failure are lacking. The cytokine storm observed in this pandemic can be a culpit in many of the observed mechanisms and presentations of this infection.